RETRACTED: Determination of the useful working coefficient (UWC) of the heating system - Abdulkhaev Zokhidjon; Abdujalilova Shairakhon; Usmonov Mavlonbek; Askarov Khasanboy; Nazirova Raxnamoxon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001